An island‐arc tectonic setting for the Neoarchean Sonakhan Greenstone Belt, Bastar Craton, Central India: Insights from the chromite mineral chemistry and geochemistry of the siliceous high‐Mg basalts (SHMB). (9th August 2017) - Manu Prasanth, M.P.; Hari, K.R.; Chalapathi Rao, N.V.; Hou, Guiting; Pandit, Dinesh
Abstract : The Neoarchean Sonakhan Greenstone Belt, located in the northeastern fringes of Bastar Craton, Central India, is dominated by basalts, andesites, dacites, and rhyolites and also contains some basic rocks with very high MgO (up to 33.4 wt%). Chromite mineralization is present in these rocks along with the cumulates of olivine and clinopyoxenes. The rocks are classified as siliceous high‐magnesium basalts (SHMB) exhibiting enriched large ion lithophile elements (LILE) and light rare earth elements (LREE) relative to the high field strength elements. Elevated Th/Yb ratios and negative Nb‐Ta‐Ti anomalies in the primitive mantle normalized multielement diagram indicates a significant role of subduction‐related melts/fluids in their genesis. The chromites in SHMB have high Cr# (0.67–0.75) and moderate Mg# (0.11–0.5) values. Parental melt calculations in the chromites indicate that they are crystallized from an SHMB magma in an island‐arc setting. A plausible model for the genesis of the rocks of Sonakhan Greenstone Belt includes initial subduction of an intraoceanic lithosphere followed by eruption of lava in an oceanic environment. Continued subduction of the slab followed by slab rollback followed by the generation of SHMB parental magma, which was introduced into the basal portions of the lithosphere in which cumulates of olivine and clinopyroxene have been developed and the chromite mineralization occurred in the inter cumulus space. Final emplacement of the magma took place in a forearc suprasubduction‐zone environment with SHMB signature carrying the cumulates, which were located in the lower part of the lithosphere.